2015
DOI: 10.18632/oncotarget.3340
|View full text |Cite
|
Sign up to set email alerts
|

miR-372inhibits p62 in head and neck squamous cell carcinomain vitroandin vivo

Abstract: Here we showed that exogenous miR-372 expression and knockdown of p62 (sequestosome1 or SQSTM1), both increased migration of head and neck squamous cell carcinoma (HNSCC) cells. p62 induced phase II detoxification enzyme NADPH quinone oxidoreductase 1 (NQO1), which decreased ROS levels and cell migration. Also, miR-372 decreased p62 during hypoxia, thus increasing cell migration. Levels of miR-372 and p62 inversely correlated in human HNSCC tissues. Plasma levels of miR-372 was associated with advanced tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 49 publications
2
47
0
2
Order By: Relevance
“…These indicate that miR‐372 induces the loss of phosphorylation in ULK1 on Ser 555, and has a regulatory role in HPAC cell autophagy. A previous study also reported that miR‐372 inhibits P62 in head and neck squamous cell carcinoma in vitro and in vivo . Jin et al .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These indicate that miR‐372 induces the loss of phosphorylation in ULK1 on Ser 555, and has a regulatory role in HPAC cell autophagy. A previous study also reported that miR‐372 inhibits P62 in head and neck squamous cell carcinoma in vitro and in vivo . Jin et al .…”
Section: Discussionmentioning
confidence: 76%
“…A previous study also reported that miR-372 inhibits P62 in head and neck squamous cell carcinoma in vitro and in vivo. (34) Jin et al report that YY1 was stimulated to promote P62 expression and subsequent autophagy activation by suppressing miR-372 expression, (35) Increasing P62 promotes tumorigenesis while inhibition of autophagy prevents tumor growth in nude mice. (36) However, the mechanism of how autophagy is activated under different conditions remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…19,22 Overexpression of miR-372 can cause the cell proliferation in HNSCC. 32 In addition, functional analysis has demonstrated that expression of miR-372 and miR-373 in tumor cells promotes proliferation and tumorigenesis through targeting the tumor suppressor gene, LATS. 17 These results suggest that miR-372 and miR-373 contribute to oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…SQSTM1 gene transcription is induced by NRF2 and NF‐κB , both of which are also activated by p62, thus establishing two interlocked positive feedback loops. SQSTM1 mRNA expression is also regulated by Ras‐ERK and JNK signaling as well as by miR‐372 and the nuclear hormone receptor farnesoid X receptor (FXR) . In addition to inflammation and oxidative stress, which activate NF‐κB and NRF2, respectively, SQSTM1 mRNA expression is induced by endoplasmic reticulum (ER) stress .…”
Section: Regulation Of P62 Expressionmentioning
confidence: 99%